Sink or swim: Phylogenomic analysis of Baikal sculpins reveals multiple transformations to pelagic, bathybenthic, and lotic ecomorphologies - Michael W. Sandel; Andres Aguilar; Sergei Kirilchik; David A. Neely; Bakhtiar E. Bogdanov; Kayla M. Fast; Joshua D. Millwood (Molecular Phylogenetics and Evolution, 2025)

Applying genetic technologies to combat infectious diseases in aquaculture - Nicholas A. Robinson; Diego Robledo; Lene Sveen; Rose Ruiz Daniels; Aleksei Krasnov; Andrew Coates; Ye Hwa Jin; Luke T. Barrett; Marie Lillehammer; Anne H. Kettunen; Ben L. Phillips; Tim Dempster; et al. (Reviews in Aquaculture, 2023)
Disease and parasitism cause major welfare, environmental and economic concerns for global aquaculture. In this review, we examine the status and potential of technologies that exploit genetic variation in host resistance to tackle this problem. We argue that there is an urgent need to improve understanding of the genetic mechanisms involved, leading to the development of tools that can be applied to boost host resistance and reduce the disease burden. We draw on two pressing global disease problems as case studies—sea lice infestations in salmonids and white spot syndrome in shrimp. We review how the latest genetic technologies can be capitalised upon to determine the mechanisms underlying inter‐ and intra‐species variation in pathogen/parasite resistance, and how the derived knowledge could be applied to boost disease resistance using selective breeding, gene editing and/or with targeted feed treatments and vaccines. Gene editing brings novel opportunities, but also implementation and dissemination challenges, and necessitates new protocols to integrate the technology into aquaculture breeding programmes. There is also an ongoing need to minimise risks of disease agents evolving to overcome genetic improvements to host resistance, and insights from epidemiological and evolutionary models of pathogen infestation in wild and cultured host populations are explored. Ethical issues around the different approaches for achieving genetic resistance are discussed. Application of genetic technologies and approaches has potential to improve fundamental knowledge of mechanisms affecting genetic resistance and provide effective pathways for implementation that could lead to more resistant aquaculture stocks, transforming global aquaculture.

Genomic and phenotypic effects of inbreeding across two different hatchery management regimes in Chinook salmon - Charles D. Waters; Jeffrey J. Hard; David E. Fast; Curtis M. Knudsen; William J. Bosch; Kerry A. Naish (Molecular Ecology, 2020)
Genomic approaches permit direct estimation of inbreeding and its effect on fitness. We used genomic‐based estimates of inbreeding to investigate their relationship with eight adult traits in a captive‐reared Pacific salmonid that is released into the wild. Estimates were also used to determine whether alternative broodstock management approaches reduced risks of inbreeding. Specifically, 1,100 unlinked restriction‐site associated (RAD) loci were used to compare pairwise relatedness, derived from a relationship matrix, and individual inbreeding, estimated by comparing observed and expected homozygosity, across four generations in two hatchery lines of Chinook salmon that were derived from the same source. The lines are managed as “integrated” with the founding wild stock, with ongoing gene flow, and as “segregated” with no gene flow. While relatedness and inbreeding increased in the first generation of both lines, possibly due to population subdivision caused by hatchery initiation, the integrated line had significantly lower levels in some subsequent generations (relatedness: F 2 –F 4 ; inbreeding F 2 ). Generally, inbreeding was similar between the lines despite large differences in effective numbers of breeders. Inbreeding did not affect fecundity, reproductive effort, return timing, fork length, weight, condition factor, and daily growth coefficient. However, it delayed spawn timing by 1.75 days per one standard deviation increase in F (~0.16). The results indicate that integrated management may reduce inbreeding but also suggest that it is relatively low in a small, segregated hatchery population that maximized number of breeders. Our findings demonstrate the utility of genomics to monitor inbreeding under alternative management strategies in captive breeding programs.

Breeding success of four male life history types of spring Chinook Salmon spawning in an artificial stream - Steve L. Schroder; Curtis M. Knudsen; Todd N. Pearsons; Todd W. Kassler; Edward P. Beall; Sewall F. Young; David E. Fast (Environmental Biology of Fishes, 2012)

Optical mapping of V m and Cai 2+ in a model of arrhythmias induced by local catecholamine application in patterned cell cultures - David Z. Lan; Andrew E. Pollard; Stephen B. Knisley; Vladimir G. Fast (Pflügers Archiv - European Journal of Physiology, 2007)